Monoposto racecar wheel aerodynamics: investigation of near-wake structure and support-sting interference - Knowles, R. D. (Cranfield University, 2007)
Monoposto racecar development is routinely carried out using wheels supported not by the car suspension but by individual, externally-mounted stings. The interference effect of these stings was acknowledged but unquantified in the existing literature. Appraisal of the literature has found that the structure of a wheel wake was not understood, rendering it difficult to assess the support sting interference. These two issues were thus jointly addressed using experimental and computational methods. The two phases of this project each tested a different industrially-representative racecar wheel model. Phase One investigated a single wheel and sting combination, whilst Phase Two extended the work to include two further stings and a model racecar. Non-intrusive velocity measurements were made in the near wakes of the various combinations to extract vertical planes, perpendicular to the tunnel freestream. The measurements made behind the isolated wheels were used to investigate the main flow features of the wake. The flow surrounding an unsupported wheel was established computationally and used to evaluate the interference effects of the support sting. Different wheel support methods (three stings and the car suspension) were used to provide further insight into the sting interference effects and also the impact of sting design on those effects. Testing with and without the model racecar allowed evaluation of its effect on the wheel wake and sting interference. The main characteristics of the near-wake of an isolated wheel rotating in ground contact are proposed from analysis of the data generated in this study. A simplified model of the trailingvortex system induced in the wake of such a wheel is proposed to clarify contradictory literature. The specific interference effects of a wheel support sting are proposed with reference to the main characteristics of the wake. The mechanisms behind these effects are, where possible, identified and presented. The main impact of the support sting, and thus the root of several of the observed effects, is the modification of the axial flow through the wheel. The main effects of the presence of the car on the near-wake are proposed alongside the observation that the wake structure is not fundamentally different to that of an isolated wheel. The proposed sting interference effects are also observed in the presence of the car, albeit at a reduced level.